Mental health of the brazilian population in the COVID-19 (SARS-CoV-2) context: literature review - Marinho, Ana Lilian de Aguiar (2021)
This study aims to reflect on the mental health of the Brazilian population during the coronavirus pandemic (SARS-CoV-2) by an integrative literature review. It ponders on mental health as a public health issue in a pandemic beyond the biological and social harm. To this end, we accessed databases Medical Literature Analysis and Retrieval System Online (MEDLINE), Scientific Electronic Library Online (SciELO), and Latin American and Caribbean Health Sciences Literature (LILACS) between July 15 and August 15, 2020 searching for Brazilian works on the topic. We identified that the most common feelings in the population are anxiety, stress, depression, and altered sleep patterns, caused mainly by the fear of falling ill and dying. The groups most affected by these feelings are the health professionals who are at the forefront of the fight against the coronavirus and people with pre-existing mental disorders. Factors such as social determinants, fake news, and social distancing are among the main factors responsible for increasing these feelings in the people. The behavior of the population also changed regarding the increased consumption of alcoholic beverages. In conclusion, a greater care to the population’s mental health is needed so that the pandemic’s impacts are not as long-lasting as reported in the studies.